2016
DOI: 10.1007/s12035-016-9810-9
|View full text |Cite
|
Sign up to set email alerts
|

The Association of SNAP25 Gene Polymorphisms in Attention Deficit/Hyperactivity Disorder: a Systematic Review and Meta-Analysis

Abstract: Attention deficit/hyperactivity disorder (ADHD) is one of the most highly heritable psychiatric disorders in childhood. The risk gene mutation accounts for about 60 to 90 % cases. Synaptosomal-associated protein of 25 kDa (SNAP-25) is a presynaptic plasma membrane protein which is expressed highly and specifically in the neuronal cells. A number of evidences have suggested the role of SNAP-25 in the etiology of ADHD. Notably, the animal model of coloboma mouse mutant bears a ∼2-cM deletion encompassing genes i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 119 publications
1
30
0
Order By: Relevance
“…In a linkage study, two polymorphisms located in the 3′-untranslated region of the human SNAP gene were associated with ADHD [48]. Additional evidence for a role of SNAP25 in ADHD was provided by a recent meta-analysis [49]. In SCZ, the structure of the hippocampus is abnormal, and a decrease in the amount of SNAP25 has been observed in the hippocampus and areas of the cortex of patients with this disease [44, 46, 47].…”
Section: Presynaptic Proteinsmentioning
confidence: 99%
“…In a linkage study, two polymorphisms located in the 3′-untranslated region of the human SNAP gene were associated with ADHD [48]. Additional evidence for a role of SNAP25 in ADHD was provided by a recent meta-analysis [49]. In SCZ, the structure of the hippocampus is abnormal, and a decrease in the amount of SNAP25 has been observed in the hippocampus and areas of the cortex of patients with this disease [44, 46, 47].…”
Section: Presynaptic Proteinsmentioning
confidence: 99%
“…The product of SNAP25, a presynaptic plasma membrane protein, is a key protein for the docking and fusion of synaptic and other vesicles (Veit Michael, Söllner Thomas H. & Rothman James E., 1996). It is suggested that high levels of expression of this gene in specific areas of the adult brain are related to nerve terminal plasticity (Oyler et al, 1989;Osen-Sand et al, 1993 Manuscript to be reviewed disorder (Liu et al, 2017). Since creativity is a complex cognitive process, these discoveries provided hints for the relation between rs362584 and creativity.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on childhood ADHD on the role of dopaminergic and serotonergic genes as well as genes involved in synaptic plasticity (107,138), have repeatedly been replicated, although effect sizes are small. Other studies, such as recent meta-analysis, involve SNAP-25 (a cellular calcium modulator) polymorphism (139). Candidate gene studies identified both similarities and differences between genetics of childhood and adult ADHD (12).…”
Section: Molecular Geneticsmentioning
confidence: 99%